International Relations / The Global Condition in the Late Twentieth Century - Pearson Frederic S; Rochester Martin J (Random House, 1988)
Introduction, The Study of International Relations and or Getting a Handle on the World, A Glimpse Into the Past: The Historical Development of the International System, A Bird's Eye View of the Present: The Contemporary International System, National Actors and International Interactions, Describing Foreign Policy Behavior: What Is It Nation-States Do?, Explaining Foreign Policy Behavior: Why Do Nation-States Do What They Do?, The Foreign Policy Process: A View from the Inside, Playing the Game of International Relations: Diplomacy Before Force, Breakdown in the Game: The Resort to Armed Force, International Institutions, International Law: Myth or Reality?, International Organizations: Links Between Governments and Between Peoples, The Global Condition: The Politics of Global Problem Solving, The Control of Violence: Combatting International Terrorism, The Promotion of Prosperity: Keeping the World Economy Running, Economic Development: The Call for a New International Economic Order